EVALUASI PRESTASI BELAJAR MAHASISWA TERHADAP PERILAKU BELAJAR DAN MOTIVASI BELAJAR MAHASISWA DI PERGURUAN TINGGI KOTA PADANG PROVINSI SUMATERA BARAT - Prima Yulianti; Mellyna Eka Yan Fitri (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2017)
The college students as an input in university have different attitudes and different assessments on teaching-learning process from one to another. This is due to differences in personal experience, family background, and culture. This is reflected in the students learning and motivation behavior. Population of the study are active student and sample was taken from several public universities and several private universities in Padang, West Sumatera. The sample was taken about 358 students. This study aims to determine the effect of learning behavior and learning motivation on student achievement, establish the factors of learning behavior and learning motivation that must be considered in order to increase student achievement. The Results of this study found that learning behavior and learning motivation influence student achievement at the significance level 5%. The other analysis obtained three factors for learning behavior (the process factors in learning, encouragement in learning and skills in Learning) and the three factors for motivation learning (diligence in learning, focus on interest in learning and learning inhibitors of motivation. This study also design a strategy to improve the achievement of student.